2013
DOI: 10.5505/tjtes.2013.48457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Piperine in Experimental Intestinal Ischemia Reperfusion Model on Rats

Abstract: BACKGROUND: Piperine is a spice principle, and its protective role against oxidative damage and lipid peroxidation has been reported. In this study, we aimed to investigate the effects of piperine in the prevention of ischemia-reperfusion injury to the small intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Moreover, PIP pre‐treatment was reported to reduce oxidative stress, inflammation and apoptosis in DOX‐induced cardiotoxicity 13 . Interestingly, the latest study has indicated that PIP exerts pivotal effects on the pathological process of I/R as well 20,21 . For instance, in a rat model of cerebral I/R injury, Zou et al 32 uncovered that PIP pre‐treatment protected neurocytes from I/R damages by regulating complement and coagulation cascades.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, PIP pre‐treatment was reported to reduce oxidative stress, inflammation and apoptosis in DOX‐induced cardiotoxicity 13 . Interestingly, the latest study has indicated that PIP exerts pivotal effects on the pathological process of I/R as well 20,21 . For instance, in a rat model of cerebral I/R injury, Zou et al 32 uncovered that PIP pre‐treatment protected neurocytes from I/R damages by regulating complement and coagulation cascades.…”
Section: Discussionmentioning
confidence: 99%
“…13 Interestingly, the latest study has indicated that PIP exerts pivotal effects on the pathological process of I/R as well. 20,21 For instance, in a rat model of cerebral I/R injury, Zou et al 32 Timely and effectively reperfusion acts as most efficacious remedy for AMI. 4,6 However, accompanying MIRI largely offset this beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slow progress has been made in understanding the causes and pathogenesis of atherosclerosis. This is largely because of the complex causes of atherosclerosis, slow progression of the disease, and lack of symptoms in the early stage (Akyildiz et al, 2013). Thus, somatic data obtained in most previous studies are mostly cross-sectional, and it is difficult to determine their causal relationship; atherosclerosis lesions in many animal models develop quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological preconditioning (PPC), known to have protective effects against IR damage, similar to IPC, has been studied with many agents thought to be effective in the intestinal tract by different mechanisms [7][8][9] .…”
Section: ■ Introductionmentioning
confidence: 99%